2010
DOI: 10.1021/jm901802n
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Clinical Evaluation of 1-{N-[2-(Amidinoaminooxy)ethyl]amino}carbonylmethyl-6-methyl-3-[2,2-difluoro-2-phenylethylamino]pyrazinone (RWJ-671818), a Thrombin Inhibitor with an Oxyguanidine P1 Motif

Abstract: We have identified RWJ-671818 (8) as a novel, low molecular weight, orally active inhibitor of human alpha-thrombin (K(i) = 1.3 nM) that is potentially useful for the acute and chronic treatment of venous and arterial thrombosis. In a rat deep venous thrombosis model used to assess antithrombotic efficacy, oral administration of 8 at 30 and 50 mg/kg reduced thrombus weight by 87 and 94%, respectively. In an anesthetized rat antithrombotic model, where electrical stimulation of the carotid artery created a thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The primary structures and activities of 177 TIs were taken from the literature [ 5 13 ]. Inhibitory activities were collected and transformed into log(10 3 /Ki) values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary structures and activities of 177 TIs were taken from the literature [ 5 13 ]. Inhibitory activities were collected and transformed into log(10 3 /Ki) values.…”
Section: Methodsmentioning
confidence: 99%
“…The discovery of small molecule TIs is an important goal for anti-thrombotic therapy [ 4 ]. In the last years, potent and selective inhibitors have been reported, such as pyridones, acetamides, oxyguanidines, aminopiperidines, amidines, and amidinohydrazones [ 5 13 ]. These sets have shown that subtle structural differences in compounds (due to the presence of similar scaffolds or the same scaffolds with different substituents) can lead to big differences in their thrombin inhibitory activities.…”
Section: Introductionmentioning
confidence: 99%
“…Other basic, but non-amidinic inhibitors have also been studied in the clinic: MCC-977 (12, sofigatran; Scheme 5) [24] from Mitsubishi Tanabe Pharma, with an aminocyclohexyl residue as S1 binder, entered Phase II studies in 2003, but the development was terminated in November 2007. Scientists from Johnson & Johnson recently reported inhibitors with an oxyguanidinyl P1 residue, which have a significantly reduced pK a value of 7-7.5 compared to that of guanidine (pK a [13][14]: [25] thus RWJ-671818 (13) shows not only high efficacy in various in vivo thrombosis models but also high bioavailabil-ity after oral dosage in dogs. Because of the advantageous preclinical profile, RJW-671818 was investigated in healthy subjects during Phase I studies, which were completed successfully.…”
Section: Thrombin Inhibitorsmentioning
confidence: 99%
“…These reactions are similar to those described for other 3-bromo- and 3-chloropyrazinonones. 17,18 A parallel set of reactions with 1,3-dibromopyrazinone 10 (Scheme 2) led to reaction products with substitution occurring exclusively at the imidoyl bromide (position 3). These are exemplified by 3-alkoxy-1-bromo pyrazinones 13 and 14 and 3-alkylamino-1-bromo pyrazinones 21–26 which were all produced in high yields.…”
mentioning
confidence: 99%
“…We note that the pyrazinone heterocycle appears to be quite chemically and metabolically stable, and that structurally diverse 3-aminopyrazinones possess a variety of of biological activities. 1719 In this respect, we tested 15–27 for cytotoxicity and for activity against a panel of protozoan parasites including Trypanosoma cruzi , Leishmania donovani , Plasmodium falciparum , and Trypanosoma brucei rhodesiense . None of the pyrazinones had notable activity against T. b. rhodesiense (IC 50s >70 μM) or T. cruzi (IC 50s >23 μM).…”
mentioning
confidence: 99%